Confession by a suspect in illicit trafficking in narcotic drugs and participation in organized criminal activities in this sphere as one of investigative situations in investigating this category of criminal cases - Chistova L. E. (Interactive science, 2017)
the article examines one of the investigative situations that can arise in the investigation of illicit trafficking in narcotic drugs committed by members of organized criminal activity in this sphere. The author's program of investigator’s actions at the initial stage of the investigation is given.
Keywords: расследование преступлений; наркотические средства; narcotic drugs; investigation of crimes; программа действий следователя; следственная ситуация; investigative situation; program for investigator’s actions